PENGARUH KINERJA KEUANGAN, KUALITAS AUDIT, DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA (Media Riset Akuntansi, 2022)
This research aims to analyze the effect of company size, profitability, leverage, and audit quality on earnings management. This study uses four independent variables, namely profitability, firm size, leverage and audit quality. While the dependent variable in this study is earnings management. The population of this study is the transportation subsector companies listed on the Indonesia Stock Exchange in the period 2016-2019. The sampling technique used in this study was purposive sampling. By using the smpling technique, 72 research samples were obtained. Data analysis was performed using multiple linear regression test. Based on the results of the study, it shows that company size, profitability, and audit quality have no effect on earnings management. Meanwhile, leverage has an effect on earnings management.